1992
DOI: 10.1152/ajpheart.1992.263.2.h429
|View full text |Cite
|
Sign up to set email alerts
|

Production of angiotensins I and II at tissue sites in intact pigs

Abstract: To estimate the contribution of angiotensin (ANG) I and II production at tissue sites to the circulating levels, ANG I and II and their radiolabeled counterparts were measured in arterial and venous plasma across various vascular beds during constant infusion of 125I-ANG I into the left cardiac ventricle of anesthetized pigs. In the combined systemic vascular beds, ANG I production was closely correlated with plasma renin activity (PRA) and ANG II production was greater than in the lungs. In the lungs virtuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 0 publications
2
51
0
3
Order By: Relevance
“…Plasma Ang I and II in untreated pigs were within the normal range. 19 No significant differences were observed between aortic and coronary venous plasma.…”
Section: Endogenous Angiotensins In Cardiac Tissue and Plasmamentioning
confidence: 89%
“…Plasma Ang I and II in untreated pigs were within the normal range. 19 No significant differences were observed between aortic and coronary venous plasma.…”
Section: Endogenous Angiotensins In Cardiac Tissue and Plasmamentioning
confidence: 89%
“…D, Cell density in the neointima was significantly higher in the BB F2 rats than in the LL F2 rats, whereas no differences were observed in the media. pulmonary vascular bed is well known to be the primary site for the "in vivo" conversion of plasma angiotensin I, 54,55 and it has been suggested that the majority of plasma ACE is released by the pulmonary ECs. 49 On the other hand, there are no significant differences in the plasma renin activity and the plasma angiotensinogen, angiotensin I, and angiotensin II concentrations between the two strains.…”
Section: Discussionmentioning
confidence: 99%
“…After an initial 30-minute period of baseline perfusion, perfusate for measurement of peptides was collected after 3,6,9,12,15,20,25,30,35,40, and 45 minutes. All perfusate samples were collected over a period of 9 seconds in the presence of a cocktail containing 26 mmol/L phenanthroline (Sigma Chemie), 125 mmol/L EDTA (Sigma Chemie), and a human specific renin inhibitor (remikiren, Hoffmann-La Roche) (10 Ϫ5 mol/L) to prevent any Ang formation outside the hindlimb.…”
Section: Hindlimb Perfusionmentioning
confidence: 99%
“…In fact, the tissues are the major site of Ang I and Ang II formation, and the release of locally formed Ang II contributes to the circulating levels of these peptides. [1][2][3] Kidney-derived renin is the major source of tissue renin. 4 Renin can be taken up by several tissues to react locally with its substrate angiotensinogen (Aogen).…”
mentioning
confidence: 99%